Bamboo Design As A Material Alternative Building And Construction In Earthquake Area Case Study: Home Karo Regency - Novalinda Novalinda; Nasution I N (International Conference on Engineering and Technology Development (ICETD), 2017)
the damage to a home or building by earthquake is an unbiased disaster avoided. The earthquake which occurred in a mountainous area, the coast or a particular place on the Earth. This is because the movement of the tectonic plates of the Earth or the effects of the eruptions. As a result a lot of loss of life, homes and buildings were destroyed. This research was conducted with the aim to get the model design of the shape of the Foundation, columns or pillars and floors of bamboo as a material for home living in earthquake-prone areas in particular sub Brastagi Karo Regency. The method used is descriptive-analytical approach by analyzing the existing design or shape of a conventional design that focuses on the form of the Foundation elements, columns, walls and floors in the House. The results of this study are highly expected to become recommendations to be forwarded on the application and testing research on next. Keywords: Earthquakes, Models, Designs, Descriptive-Analytic Housing.